2014
DOI: 10.1136/jclinpath-2014-202348
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600 co-testing in thyroid FNA cytology: short-term experience in a large cancer centre in the UK

Abstract: BRAF V600 mutational analysis can enable single-stage total thyroidectomy for carcinoma if gene mutation is present in preoperative FNA. BRAF V600 co-testing may reduce the need for completion thyroidectomy with implied cost savings and lower patient morbidity associated with completion thyroidectomy when the cytology is inconclusive but where BRAF V600 mutation is identified in preoperative thyroid FNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…Two recent studies evaluated the role of BRAF testing in thyroid cytology. Poller et al [41] demonstrated that BRAF cotesting of thyroid aspirates classified as SFM identified a subset of tumors (40%) that were BRAF -mutated. Potentially, these tumors would be managed as malignant (total thyroidectomy), avoiding the costs and risks related to a secondary neck surgery (completion thyroidectomy).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies evaluated the role of BRAF testing in thyroid cytology. Poller et al [41] demonstrated that BRAF cotesting of thyroid aspirates classified as SFM identified a subset of tumors (40%) that were BRAF -mutated. Potentially, these tumors would be managed as malignant (total thyroidectomy), avoiding the costs and risks related to a secondary neck surgery (completion thyroidectomy).…”
Section: Discussionmentioning
confidence: 99%
“…14 studies were conducted in the USA [69]. All studies were conducted between 2004 and 2014 and the number of patients ranged from 10 to 6,402 with a mean age of 47.5 (Tables 1 and 2).…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…4 The use of intraoperative FS has long been debated secondary to concerns about increased cost and operative time without a true consensus. 13,14 In 24 This is a challenging and controversial diagnosis as these tumors have no invasion and the diagnosis of cancer rests exclusively on finding the characteristic nuclei, assessment of which in many cases is subjective, leading to consistently high interobserver variability. In addition, dependence on FNA interpretation to guide surgical management without IFS was investigated.…”
Section: Introductionmentioning
confidence: 99%